Marine litter colonization: Methodological challenges and recommendations - De-la-Torre, Gabriel Enrique; Romero Arribasplata, Maggy Belén; Lucas Roman, Virna Alisson; Póvoa, Alain Alves; Walker, Tony R. (Frontiers in Marine Science, 2023)
Marine litter colonization by marine invertebrate species is a major global concern resulting in the dispersal of potentially invasive species has been widely reported. However, there are still several methodological challenges and uncertainties in this field of research. In this review, literature related to field studies on marine litter colonization was compiled and analyzed. A general overview of the current knowledge is presented. Major challenges and knowledge gaps were also identified, specifically concerning: 1) uncertainties in species identification, 2) lack of standardized sampling methodologies, 3) inconsistencies with the data reported, and 4) insufficient chemical-analytical approaches to understand this phenomenon. Aiming to serve as a guide for future studies, several recommendations are provided for each point, particularly considering the inaccessibility to advanced techniques and laboratories.